The role of the family in strengthening cyber security to confront electronic extortion - Alsuwaidi, Sharifa; Noufal, Zezit (Al-Adab Journal, 2023)
The current study aimed to reveal the role of the family in strengthening cyber security to confront electronic extortion. To achieve the objectives of the study, the qualitative approach was used. The study sample consisted of (15) respondents who are working in the Sharjah Police, Social Support Center and Child and Women Protection Center in the Emirate of Sharjah. They were intentionally selected, and the in-depth interview was used as a study tool.The results of the study concluded that the family has a major role in exposing one of its members to electronic extortion, and this occurs when there is a dysfunction in the family represented in the absence of family control, family disintegration, Family neglect, the absence of dialogue, discussion and emotional containment, in addition to the family's lack of awareness of cybersecurity and digital safety measures while using the Internet. The study showed that the family discovers that one of its members has been exposed to electronic blackmail through the changes that occur in his behavior and personality, as he suffers from social and psychological effects as a result of his exposure to blackmail. The study emphasized that the family has a very important role in protecting its children from cybercrime. The study also showed how the family strengthens the cybersecurity of its children to confront electronic extortion, by parents developing their security culture on digital safety measures so that they can transfer this security culture to their children, benefit from parental services and electronic filters in various applications, and prevent children from dealing with Strangers on the Internet, containing children emotionally, strengthening family bonds with them, making sure to follow and monitor them, and constantly discussing with them about digital safety and the safe use of the Internet.